Virus-mediated Autoimmunity, Immune Tolerance and Biologic Treatment - Habib, Arslan; Iqbal, Riffat; Taj , Muhammad Usman; Jahangir, Rabia; Rehman, Abdul; Batool, Ansa; Jafar , Haleema Sadia; Arshid , Abubakar Muhammad; Murtaza, Shumaila; Dita, Shamim Allah (Research Aspects in Biological Science Vol. 9, 2022)
Different types of human chronic diseases can develop the autoimmune disease process. Autoimmunity is the third most common cause of illness and mortality in the Western World as a set of disorders. However, the mechanism of most autoimmune disorders remains unknown. Aside from genetic variables and cytokine activity, viral infection is the most important factor in the development of autoimmune disorders. Various methods have been postulated through which viral infection could disrupt self-tolerance and initiate an autoimmune cascade, eventually leading to the destruction of a specific kind of cell or a whole-body organ. The autoimmune attack can be understood through the different immune systems and other possible mechanisms such as molecular mimicry, bystander activation and epitope spreading. Other environmental variables, including as bacterial, parasite, and fungal infections, are implicated in addition to genetic and viral influences. Various animal models, however, have been tested and provide compelling evidence that viruses caused AIDs as well as accelerated and enlarged lesions in settings where self-tolerance was disrupted. In this review, we explored virus-induced autoimmunity and the molecular mechanism that underpins this occurrence. We also covered the several viruses that affect the development of AIDs as well as its biologic treatment, such as rubella virus, enteroviruses, measles virus, human T-lymphotropic virus type 1, human cytomegalovirus, human herpes virus-6, Epstein-Barr virus, rotavirus, and others.